Collaboration for clinical innovation: a nursing and engineering alliance for better patient care. (May 2020) - Andrews, Rachael; Greasley, Sarah; Knight, Sarah; Sireau, Sonya; Jordan, Andrea; Bell, Andrew; White, Paul
Background: There is significant need and enormous potential for innovation in clinical settings. However, for various reasons, this potential is rarely realised. Aims: This paper aims to present a collaborative approach to innovation between clinicians and engineers, using two nursing case studies as examples. Suggestions are offered to improve facilitation of innovation in healthcare settings. Methods: An engineering design process was applied to develop novel medical devices in response to unmet clinical needs identified by nurses. This process includes problem exploration, definition of project scope, concept generation, detailed design, manufacture, prototype evaluation and iterative design improvements. Results: Two case studies are presented to showcase the results of this multidisciplinary approach to innovation. Both projects resulted in novel medical devices being put into clinical use safely and effectively. Conclusions: Collaboration between nurses and engineers facilitates rapid iteration of novel solutions to unmet clinical needs. Both professions have similar approaches to problem-solving, complemented by specialist knowledge in their contrasting areas of expertise, making for a highly capable multidisciplinary team.